2016
DOI: 10.1002/adma.201602423
|View full text |Cite
|
Sign up to set email alerts
|

Green Processing of Carbon Nanomaterials

Abstract: Carbon nanomaterials (CNMs) from fullerenes, carbon nanotubes, and graphene are promising carbon allotropes for various applications such as energy-conversion devices and biosensors. Because pristine CNMs show substantial van der Waals interactions and a hydrophobic nature, precipitation is observed immediately in most organic solvents and water. This inevitable aggregation leads to poor processability and diminishes the intrinsic properties of the CNMs. Highly toxic and hazardous chemicals are used for chemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
39
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(39 citation statements)
references
References 223 publications
(323 reference statements)
0
39
0
Order By: Relevance
“…To enhance not only their electrical and photophysical properties, but also their solubility, the covalent and noncovalent functionalization of CNTs has been intensively investigated. Much attention has been paid to the covalent functionalization, which lends a new function to CNTs; to some extent, it reduces the π‐conjugation of pristine CNTs . However, only a limited number of noncovalent functionalization methods involving supramolecular interaction with CNTs, and which have no significant effect on the π‐system, have been considered to date.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To enhance not only their electrical and photophysical properties, but also their solubility, the covalent and noncovalent functionalization of CNTs has been intensively investigated. Much attention has been paid to the covalent functionalization, which lends a new function to CNTs; to some extent, it reduces the π‐conjugation of pristine CNTs . However, only a limited number of noncovalent functionalization methods involving supramolecular interaction with CNTs, and which have no significant effect on the π‐system, have been considered to date.…”
Section: Introductionmentioning
confidence: 99%
“…Functionalization of the outside of CNTs, achieved by supramolecular interaction of π‐conjugated small molecules and polymers, has recently been investigated, although supramolecularly functionalized materials are inherently labile. [2a,5] Interlocked supramolecular complexes of CNTs with cyclic compounds are considered to be applicable as 2D and 3D networks of nanowires and disease‐specific theranostic agents having multiple functionalities.…”
Section: Introductionmentioning
confidence: 99%
“…15,16 These usually include high boiling point and non-innocuous organic solvents, such as N-methyl-2-pyrrolidone, N,N-dimethylformamide or cyclopentanone. However, with a view to a greener production and processing of graphene, the use of water as the solvent medium is clearly preferable, 17,18 but its surface energy is much higher than that of graphite/graphene. Thus, even though some recent reports have shown that pristine graphite can be exfoliated and dispersed in water under neutral or basic conditions, [19][20][21] the concentration of the resulting graphene dispersions is too low (< 0.02 mg mL -1 ) to be of far-reaching practical relevance.…”
Section: Introductionmentioning
confidence: 99%
“…[22][23][24][25] Recently, our group synthesized a new near-infrared ratiometric fluorescence probe that was used to achieve visualizable real-time tracing of the concentration changes of ROS in mice and in situ tracking of inflammation through in vivo fluorescence imaging. [28,29] As a member of the carbon nanomaterials family, carbon nanodots have many advantages such as high fluorescence intensity, good photostability, resistances to photobleaching, low toxicity, and good biocompatibility, enabling them to have promising applications in bioimaging, biosensor, PDT, and drug delivery. [27] Carbon nanomaterials have been demonstrated to be a highly useful class of nanomaterials.…”
mentioning
confidence: 99%